Superior performance and Hot Carrier reliability of strained FDSOI nMOSFETs for advanced CMOS technology nodes. (November 2015) - Besnard, G.; Garros, X.; Andrieu, F.; Nguyen, P.; Van Den Daele, W.; Reynaud, P.; Schwarzenbach, W.; Delprat, D.; Bourdelle, K.K.; Reimbold, G.; Cristoloveanu, S.
Abstract: The Hot Carrier (HC) reliability of NMOS transistors fabricated on biaxially tensile-strain SOI substrates (sSOI) is compared to that of devices fabricated on standard unstrained SOI substrates. It is shown that sSOI-based devices not only exhibit a 10% higher performance in term of I ON / I OFF but also show superior HC reliability at same drive current. This reliability improvement may be explained by a better interface quality for sSOI films.